SISTEM PAKAR MENDIAGNOSA PENYAKIT TANAMAN MANGGA ARUMANIS DENGAN METODE CERTAINTY FACTOR - Sulaiman, Sulaiman; Nurhayati, Nurhayati; Sitompul, Juliana Naftali (JURNAL TEKNISI, 2021)
Diseases that attack mango plants cause mango farmers to suffer losses due to damaged crops or crop failure. To assist agricultural extension workers in diagnosing temporary diseasesthat attack mango arumanis plants if agricultural experts or experts do not exist or do not exist, a computer-based system is needed that can provide information on diseases and how to control it. This study builds a rule-based expert system using the cairtanty factor method to diagnose diseases in mango arumanis plants based on the symptoms of each diseases. The results obtained are in the form of diseases that attack and control procedures that attack and control procedures that must be carried out, as well as the certanty factor value of the truth of the diseases.